The Effect of Corporate Social Responsibility on Mining Company Tax Avoidance - Elok Nusantari; Dicky Chandra Hermawan; Murtanto Murtanto; Aris Rianto Faisal (Budapest International Research and Critics University, 2022)
The purpose of this study is to examine the impact of corporate social responsibility (CSR) on corporate tax avoidance. In this study, independent variables were used to assess disclosure of social responsibility, CSR, and the economic and social dimensions of CSR. While tax avoidance is the dependent variable in this study, as evaluated by the size of the effective tax rate. The data collected from the mining sector, which is listed on the Indonesia Stock Exchange from 2015 to 2020. Purposive sampling was used to choose the research sample; it obtains 35 companies per year that match the criteria. The purpose of this study is to determine whether CSR and its Economic and Social Dimensions influence company tax avoidance using multiple linear regression. The findings indicate that the independent variables CSR, CSR Economic dimension, and CSR Social dimension all influence tax avoidance, as measured by the effective tax rate in the mining sub-sector listed on the Indonesia Stock Exchange.